CORPORATE IDENTITY DESIGN POLICY IN THE PROCESS OF VISUAL COMMUNICATION - Apele, Diāna; Bodža, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The term corporate identity describes the essence of a company, a set of all the characteristics that make up the company. The company SIA “Nature Line” mentioned in the article, which started its operation as a start-up in the food production industry through the Rēzekne Business Incubator start-up programme, put forward as one of the company’s principal aims to promote the recognition of the company and its products to ensure broad opportunities for product export. One of the objectives for reaching the aim is to create a corporate identity design. A corporate identity design will help the company to start advertising and positioning itself to customers, thus promoting successful company operation. Considering the changing trends, technological opportunities, popularity of the start-up field, and rapid development of visual communication in the modern day, in the article the authors justify the relevance of the chosen topic. The research problem is the lack of understanding on the part of start-ups about the importance of designing a corporate identity for ensuring successful operation of the company as well as insufficient support. The research aim is to explore modern corporate identity development trends in the context of design policy and to analyse expert interviews in order to find out the opinion of experts about the importance of creating a corporate design for ensuring successful operation of a star-up company, about the trends in the graphic design of corporate identity, about the most important elements and their successful positioning. The research results are obtained using the theoretical research methods: the study of scientific and journalistic literature and internet resources, analysis and evaluation, which discover the essence of the problem, as well as expert interviews, which are empirical research methods.